Social Media Regulations and Government Censorship in Nigeria - Chinelo Ebele Uchendu; Omolara Oluwabusayo Akin-Odukoya; Funmi Falobi; Perpetua Ogechi Aondover; Louis Benard (Polit Journal Scientific Journal of Politics, 2025)
Social media regulations and government censorship in Nigeria have evolved over the years, shaped by the government’s desire to manage the influence of online platforms on public discourse, politics, and social activism. There have been discussions about regulating over-the-Top (OTT) services and, by extension, digital material all over the world. Through mandatory operational licenses or content filtering, regulators continue to try to bring OTT service providers' services inside their regulatory purview in a number of jurisdictions. It has been the same in Nigeria, one of the biggest markets for OTT services worldwide. Despite the fact that Nigerians are using social media more frequently and finding ways to communicate with one another that are less expensive than paying for phone calls, these calls for regulation continue to reverberate. The Nigerian government has expressed concern over the use of social media to commit crimes and support terrorist activities in the nation as a result of the exponential rise in social media usage among Nigerians and the country's escalating level of insecurity. The way that citizens criticize the government on numerous social media sites like Twitter and organize themselves for both online and offline rallies like the EndSARS Protest is even more concerning for the administration. The government's agenda to establish channels for social media and OTT regulations has been centered on these concerns. The paper argued that social media has an impact on society in many different nations throughout the world. Due to its role in amplifying and hastening regime changes in Tunisia, Egypt, and Libya, the Arab spring became a point of reference in numerous discourses.